(untitled) (Docentes 2.0 Journal, 2025)
In Bolivia, the increase in gender violence and bullying led to the need to re-evaluate educational strategies. The present research aimed to understand the key emotional competencies for building a culture of peace, providing an innovative perspective that effectively addresses social challenges. The research was based on a systematic method, interpretive paradigm, qualitative approach, descriptive narrative design, and meta-analysis techniques. The sample included scientific articles and degree works, both at the undergraduate and graduate levels, related to gender violence, bullying, and emotional education. The results revealed that emotional competencies, such as emotional regulation, empathy, and emotional awareness, were fundamental for the peaceful resolution of conflicts and for creating a safe, educational environment. The discussions highlighted the importance of integrating these competencies into the school curriculum to prevent violence and foster respect and coexistence. In conclusion, the research suggested that emotional education improved students’ well-being and contributed to social cohesion and the construction of a culture of peace in Bolivia. It was recommended that educational programs focused on these competencies be implemented to address current social challenges effectively.